The Racialized Costs of “Traditional” Banking in Segregated America: Evidence from Entry-Level Checking Accounts - Faber, Jacob William (Race and social problems, 2020)
A growing body of evidence shows that America’s racial geography shapes access to basic financial services (e.g. banking), highlighting a mechanism connecting segregation to economic vulnerability: spatially organized institutional marginalization.s While the practices and policies of “mainstream” commercial banks are central to this dynamic, the costs they impose on the communities they serve have been understudied. This study leverages survey data from a stratified random sample of 1344 banks across the United States to investigate variation in the costs and fees of entry-level checking accounts at commercial banks. Our evidence shows banks charge more to open and maintain checking accounts in neighborhoods and cities with larger Black and Latinx populations even after controlling for demographic and socioeconomic characteristics as well as market competition. The higher costs of banking imposed on Black and Latinx communities are further compounded by parallel disparities in income. These findings reveal the unequal costs of banking in segregated America.